Central line bundle maintenance among adults in a university hospital intensive care unit in São Paulo, Brazil: a best practice implementation project. (June 2018) - Sichieri, Karina; Iida, Luciana Inaba Senyer; Menezes, Isa Rodrigues da Silveira Cabral de; Garcia, Paulo Carlos; Santos, Talita Raquel; Peres, Emília; Shimoda, Gilcéria Tochika; Maia, Flávia de Oliveira Motta; Secoli, Silvia Regina; Püschel, Vilanice Alves de Araújo
ABSTRACT: Objectives: This implementation project aimed to identify the current practice in regards to central venous catheters (CVCs) maintenance to improve knowledge amongst nursing staff and to assess increased compliance with evidence-based best practice. Introduction: Central venous catheters are considered an important therapeutic resource for the administration of fluids, drugs, blood, collection of blood samples and hemodynamic monitoring. Despite the benefits, catheter use is associated with complications such as primary infection of the catheter-related bloodstream. Methods: This project utilized the audit and feedback model using the Joanna Briggs Institute Practical Application of Clinical Evidence System. Nine of 10 criteria were audited through direct observation of nursing professionals or patient records in relation to CVC maintenance, and one criterion involved direct questioning of nursing staff. Baseline and follow-up audits were conducted in a 12-bed adult intensive care unit in a university hospital. Results: The baseline audit revealed deficits between current practice and best practice in some criteria. Barriers to implementation of CVC maintenance best practice criteria were identified, and the strategies were implemented. The post-implementation (follow-up) audit showed improvement in compliance to best practice guidelines in all of the audit criteria, except in one criterion: the use of sterile gloves or surgical tweezers during the execution of the dressing. Conclusions: Best practice in CVC care was achieved in the hospital, strengthening and guiding nursing care, as well as highlighting the importance of nursing records throughout the care process. However, this project highlighted the need to improve compliance through follow-up audits and periodic training to support best practice.